Calreticulin, a therapeutic target?. (1st September 2016) - Eggleton, Paul; Bremer, Edwin; Dudek, Elzbieta; Michalak, Marek
ABSTRACT: Introduction : Calreticulin is an endoplasmic reticulum (ER) resident protein critical for maintaining Ca 2+ homeostasis and glycoprotein folding in the ER. The protein has also been identified on the cell surface of apoptotic and necrotic cells and implicated to play a role in immunogenic cell death and other extracellular functions. The molecular events that promote cell surface association of calreticulin are not clear. Under cell stress conditions (environmental, drug induced, hypoxia), calreticulin may be upregulated as it attempts to regulate cell survival, death or repair. The initial signaling mechanisms involved in these processes may be regulated by the unfolded protein response (UPR) and genome damage response (GDR) pathways. Area covered : Here, the phenomenon of cell surface calreticulin and its extracellular functions are discussed, with a major emphasis on the process of immunogenic cell death. The evidence of how cell surface calreticulin may act as a damage associated molecular pattern molecule is evaluated, in addition to how these properties of the protein can be exploited for therapeutic vaccine development, cancer treatment and mediating other inflammatory processes. In addition, clarification of calreticulin functions from its intracellular, cell surface, and extracellular locations are provided. Expert opinion : While the protein folding and immune-stimulatory properties of calreticulin can be exploited to develop therapies, the molecular pathways involved remain to be elucidated. Nevertheless, exploiting the multifaceted properties of calreticulin may in the future provide a means to treat a number of diseases.